Target C# : simple hands-on programming with Visual Studio 2022 - Byrne, Gerard (Apress L. P., 2022)
So, you want to learn C# and Visual Studio 2022, but are a bit intimidated? Don't be. Programming is within your grasp! Programmers at any level have to fully understand, and more importantly, be able to code the core constructs. It is impossible to use complex programming concepts such as classes before understanding what methods and variables and their data types are. Once there is a foundation built on the basics, then all other topics can fall in line. While it is a forgone conclusion that languages change with the introduction of new features, the core concepts do not. Even large enterprises do not always update to the latest versions of languages and frameworks; their "backbone" applications have been developed to work, regardless. More than ever, enterprises need developers who can master and apply the core programming concepts and then be "up-skilled" with newer language levels and features as they integrate into the company. This book builds from the ground up. You will begin with an introduction to programming, learning the foundational concepts needed to become a C# programmer. You will then put to practice a wide range of programming concepts, including data types, selection, iteration, arrays, methods, classes and objects, serialization, file handling, and string handling. You will learn enough to develop applications that emulate commercial application code. Once you've got the foundational concepts, get ready to dive into common programming routines, including linear search, binary search, bubble sort and insertion sort, and use C# to code them. Code example annotations supplement the learning and are designed to enhance learning while also explaining why the code does what it does. This book: Teaches core programming through well-explained and simple-to-follow instructions Reinforces programming skills through the use of coding examples that extend user learnings Explains theoretical programming concepts; applies them practically with code examples Introduces the latest Microsoft C# Integrated Development Environment (Visual Studio 2022) Enlists clear, precise, and easy-to-understand language to assist readers of all levels and experience Uses a mix of "theory" and practical information that is designed to be friendly and engaging Who This Book Is For Beginners, those refreshing their C# skills, or those moving from another programming language. No skills or previous knowledge is required. Readers will need to download Visual Studio 2022 Community Edition as this is what the book code has been based on, but they could use other Integrated Development Environments.